An Examination of Physical Processes That Trigger the Albedo-Feedback on Glacier Surfaces and Implications for Regional Glacier Mass Balance Across High Mountain Asia - Johnson, Eric; Rupper, Summer (Frontiers in Earth Science, 2020)
Due to their high sensitivity to changes in climate, glaciers are one of the best natural indicators of climate change. Despite this, many underlying processes that control glacier response to climate change are poorly understood. One potentially important set of such processes are feedback mechanisms that can amplify or dampen glacier melt in response to a change in climate. Though feedbacks are recognized as important processes affecting glacier mass balances, little has been done to systematically quantify their effects. This study develops a surface energy and mass balance model to quantify the contribution of the albedo-feedback to glacier mass balance. Specifically, we quantify the roles of three trigger processes that initiate the albedo-feedback: snowpack thickness, snowfall event frequency, and heat flux supplied by precipitation. The model follows common energy balance methods but includes “switches” to turn these trigger processes off. The model is applied to Chhota Shigri Glacier using meteorological inputs from three different climate regions in High Mountain Asia (HMA). The results show that up to 80% of the average glacier melt increase from a +1°C temperature change can be attributed to the albedo-feedback. Furthermore, the system gain due to the albedo-feedback depends most on snowfall event frequency and the availability of incoming shortwave radiation during the melt season, and are thus generally largest in summer accumulation settings of HMA. This sensitivity to snowfall timing and frequency results in system gains being highest near the equilibrium line altitude, where a small change in temperature can shift precipitation phase from snow to rain. Regional analysis using climatological estimates suggests that many glaciers in the monsoonal Himalayas and southern Tibetan Plateau are likely to exhibit particularly strong albedo feedbacks. These results contribute to a growing body of literature suggesting that the mass balance of summer-accumulation type glaciers is strongly controlled by summer snowfall amount and frequency, which is closely linked with changes in air temperature. It also highlights the significance of the albedo feedback on glacier mass balance and the need to further explore feedbacks associated with glacier surface processes.